Strategi Komunikasi Puskesmas Sungai PUA Untuk Meningkatkan Kesadaran Masyarakat Dalam Menanggulangi Stunting - Havivah .; Dion Eriend (CV. ITTC INDONESIA, 2026)
Stunting is a chronic nutritional problem that remains a public health challenge in Indonesia because it affects physical growth, cognitive development, and the quality of future human resources. This study aims to analyze the communication strategies of the Sungai Pua Community Health Center (Puskesmas) in raising public awareness regarding stunting prevention. The study employs a qualitative approach using descriptive methods through interviews, observations, and documentation. Research informants included the head of the community health center, nutrition staff, Posyandu cadres, pregnant women, breastfeeding mothers, and mothers of toddlers. The results indicate that communication strategies are implemented through health education sessions, Posyandu activities, home visits, the use of social media, and the involvement of Posyandu cadres as community health communicators. These strategies have successfully improved public understanding of the importance of adequate nutrition, monitoring children’s growth and development, exclusive breastfeeding, and early stunting prevention. However, the implementation of health communication still faces barriers in the form of low community participation, family economic constraints, and negative community perceptions of the term “stunting.” Therefore, more persuasive, empathetic, and sustainable communication strategies are needed so that health messages can be optimally received by the community. This study also indicates that interpersonal communication.